2018
DOI: 10.6007/ijarafms/v8-i1/3794
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Capital Flight on Exchange rate in Nigeria

Abstract: The study examined capital flight and real exchange rate in Nigeria from 1990 to 2014. The study used five independent variables (capital flight, foreign direct investment, current account balance, foreign borrowing and external reserves) and one dependent variable (real exchange rate). Test carried out include unit root test, co-integration test, causality test and ordinary least square. The study revealed that: There is positive significant relationship between foreign borrowing and real exchange rate in Nig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 3 publications
1
6
1
Order By: Relevance
“…However, this is not statistically significant in the fixed model. This result is not consistent with the findings of ahead and Nelson et al (2018), who found a positive and significant relationship between capital flight and exchange rate. Economic growth is not statistically significant and has a negative impact on capital flight in the three models.…”
Section: Resultscontrasting
confidence: 99%
“…However, this is not statistically significant in the fixed model. This result is not consistent with the findings of ahead and Nelson et al (2018), who found a positive and significant relationship between capital flight and exchange rate. Economic growth is not statistically significant and has a negative impact on capital flight in the three models.…”
Section: Resultscontrasting
confidence: 99%
“…Also, a positive relationship exists between exchange rate and GDI. Furthermore, Nelson et al (2018) examined the impact of capital flight on exchange rate in Nigeria from 1990 to 2014 using OLS techniques on the following variables: capital flight, real exchange rate, foreign direct investment, current balance, foreign borrowing, and external reserves. Results revealed that there is a negative relationship between capital flight and exchange rate.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, capital transferred abroad from a host country cannot in any way contribute to domestic investment and other productive activities. It is still unknown whether the significantly lower levels of investment with corresponding multiplier consequences on other aspects of the economy, including the growing rate of unemployment, social unrest, hunger and starvation, and general economic recession in the country, are mainly a result of capital flight (Nelson, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…They affirm that factors such as political instability, looted funds, foreign education, and foreign medical tourism are the major causes of capital flight in Nigeria. In another dimension, but closely related to Nigeriaspecific studies, Nelson et al (2018) report that capital flight has an insignificant negative interaction with capital flight in Nigeria between 1990 to 2014, while Effiom et al (2020) find evidence of a negative and significant impact of capital flight on domestic investment in Nigeria. In particular, their study documents a more severe long-run impact of capital flight on domestic investment than capital flight's short-run impact.…”
Section: Literature Reviewmentioning
confidence: 93%